A 'test and treat' prevention strategy in Australia requires innovative HIV testing models: a cohort study of repeat testing among 'high-risk' men who have sex with men. (22nd January 2016) - Wilkinson, Anna L; El-Hayek, Carol; Spelman, Tim; Fairley, Christopher K; Leslie, David; McBryde, Emma S; Hellard, Margaret; Stoové, Mark
Abstract : Objectives: HIV diagnoses among men who have sex with men (MSM) in several high-income countries, including Australia, have increased substantially over recent years. Australia, in line with global prevention strategies, has emphasised a 'test and treat' HIV prevention strategy which relies on timely detection of HIV through frequent testing by those at risk. We examined trends in repeat testing among MSM defined as 'high-risk' according to Australian testing guidelines. Methods: HIV test records from MSM attending high caseload clinics in Melbourne 2007–2013 and classified as high-risk were analysed. Binary outcomes of 'test within 3 months' and 'test within 6 months' were assigned to tests within individuals' panel of records. Negative binomial regressions assessed trends in overall HIV testing and returning within 3 and 6 months. Annualised proportions of return tests (2007–2012) were compared using two-sample z tests. Results: Across 18 538 tests among 7117 high-risk MSM attending primary care clinics in Melbourne (2007–2013), the number of annual HIV tests increased (p<0.01). Between 2007 and 2012 annualised proportions of tests with a subsequent test within 3 and 6 months also increased (p<0.01); however, by 2012 only 36.4% and 15.1% of tests were followed by another test inside 6 and 3 months, respectively. Conclusions: Repeat testing among high-risk MSM in Australia remains unacceptably low, with recent modest increases in testing unlikely to deliver meaningful prevention impact. Removing known barriers to HIV testing is needed to maximise the potential benefit of test and treat-based HIV prevention.